Detection of STRN‐ALK fusion in thyroid nodules with indeterminate cytopathology facilitates papillary thyroid cancer diagnosis. Issue 4 (21st October 2020) - Jurkiewicz, Magdalena; Cimic, Adela; Murty, Vundavalli V.; Kuo, Jennifer H.; Hsiao, Susan; Fazlollahi, Ladan; Fernandes, Helen
Abstract: Thyroid cancer is the most common endocrine malignancy. Approximately 70% of cases of papillary thyroid carcinoma and 50% of poorly differentiated and anaplastic thyroid carcinoma harbor well‐characterized driver mutations and chromosomal rearrangements that drive tumorigenesis. Molecular profiling has been helpful in identifying and informing follow‐up strategies in tumors with more aggressive trajectories. Here, we report a case of papillary thyroid cancer (PTC) discovered in a patient with thyroid nodules with relatively benign ultrasound and fine needle aspiration (FNA) findings. Molecular testing in this patient identified a rare STRN‐ALK fusion in two thyroid nodules with indeterminate and/or benign cytology. This led to the patient undergoing a thyroid lobectomy and a subsequent confirmation of papillary thyroid carcinoma upon resection. The report highlights the role of comprehensive molecular testing in thyroid lesions of indeterminate cytology.